Isoterm Adsorpsi Zat Warna Rhodamin B Menggunakan Karbon Aktif Limbah Sisik Ikan Kakap Putih (Lates calcarifer) Sebagai Adsorben - Tanasale, Matheis F.J.D.P.; Latupeirissa, Jolantje; Fransina, Eirene Grace; Muliana, Muliana (Jurnal Kimia Fullerene, 2024)
Adsorption rhodamine B dye using adsorbent of activated carbon from fish scales has been done. The study aims to determine the adsorption isotherm. Activated carbon was obtained through the process of carbonization, putting the fish scales into the furnace at 350 °C and characterized by XRD, the results showed that the three peaks with intensity in their regions were 26.45o, 32.69o, and 33.60o. It was calcined at the temperature of 450 °C and characterized by XRD. The results showed peaks shift were 26.52o, 29.66o, and 32.77o. The activation charcoal in a 3M KOH, dried in oven at 110 °C and characterized by XRD. The results showed, peaks with the highest intensity were 26.22o, 29.12o, and 32.43o, and the basal spacing is biggest than before activation. The determination of rhodamine B dye adsorption was characterized by UV-Vis spectrophotometer. The results showed that the optimum condition were 0.8 g mass adsorbent, the contact time of 100 minutes at pH of 3, and concentration of 10 ppm. The adsorption of rhodamine B dye using activated carbon from fish scales followed Freundlich isotherm with correlation coefficient (r2), KF, and n were 99.68%, 0.6298 mg/g, and 1.8685 respectively that showed fisisorption process.